"Immigrant" in Russian and French Print Media (Linguistic and Visual Composition Analyses). Issue 4 (3rd July 2016) - Permyakova, Tatiana M.; Antineskul, Olga L.
Abstract: This study addresses the representation of the linguistic and cultural type "immigrant" in French and Russian media discourse. Linguistic analysis of selected sources shows, on the one hand, signs of tolerance towards immigrants and, on the other hand, evidence of rejecting immigrants, which demonstrates the ambiguity of the matter and indirectly provokes conflicts. Visual composition analysis complements these results by revealing the following: the purpose of immigration – employment – is often socially rejected; immigrants' sense of community is a specific cultural code in a host culture; and the cultural transfer of an "immigrant" into a different space creates uncertainty or ambiguity.